(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Commercial banking industry plays a key role in investment growth, and in the development of different industries around the world. Because accounting information systems (AIS) play a key role in determining the degree of success, and affect the competition position of commercial banks in a world that characterized with globalization, these systems need more investigation. The study investigates whether the outputs of the automated accounting information systems of the Omani commercial banks are understandable, relevant, reliable, comparable, and consistent, in order to satisfy the requirements of decision makers in this group of banks. A questionnaire was developed and self-administered for a selected convenient sample of decision makers from the Omani commercial banks in order to collect the required data. T-test and a selected group of descriptive statistics were used to analyze the collected data and to test the hypothesis of the study. The study finds that the outputs of the automated AIS of the Omani commercial banks are understandable, relevant, reliable, comparable, and consistent, so these outputs are useful for the purposes of the decision making process.